CRONY CAPITALISM PRACTICES IN INDONESIA'S MINING INDUSTRY: A Critical Study Form the Islamic Economic Perspective - Sutrisno, Agung Dwi; Astuti, Meti (Mukaddimah: Jurnal Studi Islam, 2024)
This study explores the impact of crony capitalism practices in Indonesia’s mining sector from an Islamic economic perspective, focusing on wealth distribution equity and resource exploitation. The research employs a qualitative descriptive method with a content analysis approach, based on secondary data such as journal articles, company reports, and policy documents. The findings reveal that close ties between business and political elites create exclusive access to state resources, resulting in economic inequality, environmental degradation, and social injustice. From an Islamic perspective, mining resources are considered “milkiyah ‘ammah” or public ownership, which must be managed for the collective benefit. These findings are relevant in the context of contemporary Islamic studies, offering a sharia-based approach to policy reform emphasizing transparency, equitable benefit distribution, and environmental protection. This study contributes to the development of an Islamic economic framework for more equitable and sustainable resource management.